Factors Affecting Financial Statement Fraud Disclosure: Data Mining, Forensic Accounting and Investigation Audit - Nurarifah, Syifa; Kuntadi, Cris (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
Previous research or relevant research is very important in producing scientific research or articles. Previous research or relevant research has a role in strengthening theories and phenomena of the relationship or influence between variables. This article reviews factors that can influence the disclosure of fraudulent financial statements, such as forensic audits, investigative audits and data mining. This journal is a study of audit literature. The purpose of writing this scientific article is to build a hypothesis of the influence between variables to be used for further research. The results of this literature review article are: 1) data mining has an influence on the disclosure of fraudulent financial statements; 2) forensic accounting has an influence on the disclosure of fraudulent financial statements; and 3) investigative audits have an influence on the disclosure of fraudulent financial statements.